BioMag 1: A magnetic approach for efficient enzyme and microorganism reuse in biochemical processes for energy and food industries - Daniela Sánchez-Orozco; Jerry Landívar; Sócrates Palacios-Ponce; Anna Ilina; Wilson Sánchez-Macías; Livingston D. Castro (PLoS ONE, 2025)
The production of biofuels and many food products involves biochemical processes such as hydrolysis and fermentation, which are expensive processes because of the need for new enzymes and microorganisms for each new cycle of production. Furthermore, the complexity of laboratory equipment for these tests and their cost limits the development of technological solutions for the industry. To improve these production processes, the use of open-source technologies presents a promising alternative for the development of innovative tools. In this work, we developed an automated system that enhances the efficiency of hydrolysis and fermentation assays by enabling the reuse of enzymes and microorganisms, immobilized with magnetic nanoparticles. The conceptual design of the system consisted of a reservoir with inputs and outputs to control the bioengineering process. To design the electromagnet array, it was necessary to use a mathematical model of the magnetic flux behavior of the electromagnets. With this model, it was possible to determine the magnetic density and dimensioning for the detailed design. The system required the design of controllers for the temperature, pH, and revolutions to operate simultaneously. The prototype of the mechatronic system included a user interface to control and monitor these variables in real time and to record the data during the experiment. It was possible to design and build a prototype that can use the magnetic field to pull down ferromagnetic particles within a fluid. The open-source technologies helped to build this prototype at an affordable price and opened the possibilities for further improvements. Ultimately, reducing costs and overcoming technological limitations in biofuel and food production processes.